Extraforaminal Vertebral Artery Anomalies and Their Associated Surgical Implications: An Epidemiological and Anatomic Report on 1000 Patients. (16th November 2020) - Zhang, Michael; Dayani, Fara; Purger, David A; Cage, Tene; Lee, Marco; Patel, Mahesh; Singh, Harminder
Abstract: INTRODUCTION: Extraforaminal vertebral anomalies involve entry at cervical transverse foramina other than at C6 and can appear with other anatomical variations along the V2 segment. Such unexpected vessel courses can have implications on surgical planning. METHODS: We conducted a retrospective study on 1000 consecutive computed tomography angiograms, documenting level and laterality of vessel of entry, as well as vertebral dominance patterns. Patients with rostral C4 anomalies were assessed for medialization. The pedicle widths ipsilateral to caudal C7 anomalies were compared to those of contralateral and matched controls. RESULTS: A total of 157 patients were identified with extraforaminal entries, with 25 having bilateral findings. The most common alternative entry was at C5 (70.3%), followed by C4 (17.6%) and C7 (11.5%). Among patients with unilateral anomalies, there was an increased representation of contralateral vertebral dominance, relative to ipsilateral dominance (79.6% vs 20.4%, P  < .0001). Among anomalous C4 entries, vertebral medialization was seen along the right (35%) and left sides (23.1%) spanning C6-T1. Among C7 anomalous entries there was no statistical difference in pedicle width. CONCLUSION: Extraforaminal anomalies may be more frequent than previously reported and are important considerations during subaxial cervical spine surgery planning. Particular attention should be paid towards the contralateral dominance pattern within this subgroup. In patients with anomalous V2 segment entries, adherence to the standard, anatomical landmarks remains desirable.